EGFR gene copy number as a predictive biomarker for resistance to anti-EGFR monoclonal antibodies in metastatic colorectal cancer treatment: a meta-analysis - Shen, Wei-Dong; Chen, Hong-Lin; Liu, Peng-Fei (Chinese Journal of Cancer Research; Vol 26, No 1 (February 27, 2014): Chinese Journal of Cancer Research, 2014)
Objective: The epidermal growth factor receptor (EGFR) inhibitors monoclonal antibodies (MoAbs) have already shown the therapeutic effectiveness in patients with metastatic colorectal cancer (mCRC). But many patients resist to the treatment. The aim of this meta-analysis was to assess EGFR gene copy number (GCN) as a candidate predictive biomarker for resistance to anti-EGFR MoAbs in mCRC treatment. Methods: Systematic computerized searches of the PubMed, EMBase and Cochrane Library were performed. The primary endpoint was objective response rate (ORR). The second endpoints included progression-free survival (PFS), and overall survival (OS). The pooled odd ratio (OR) and pooled sensitivity, specificity, and summary receiver operator characteristic (SROC) for ORR were estimated. The pooled hazard ratios (HR) for PFS and OS were also calculated. Results: Fourteen studies with 1,021 patients were included. Increased EGFR GCN was associated with increased ORR (OR=6.905; 95% CI: 4.489-10.620). It was also found in wild-type KRAS mCRC patients, with the pooled OR of 8.133 (95% CI: 4.316-15.326). GCN has medium value for predicting ORR, with the pooled sensitivity of 0.79 (95% CI: 0.73-0.84), the pooled specificity of 0.59 (95% CI: 0.55-0.62). In wild-type KRAS mCRC patients, the sensitivity and the specificity were 0.80 (95% CI: 0.70-0.87) and 0.60 (95% CI: 0.53-0.66), respectively. Increased EGFR GCN was associated with increased PFS (HR=0.557; 95% CI: 0.382-0.732) and OS (HR=0.579; 95% CI: 0.422-0.737). Conclusions: This meta-analysis suggests that EGFR GCN represents a predictive biomarker for tumor response in mCRC patients treated with MoAbs regardless of KRAS mutation. mCRC patients with increased EGFR GCN are more likely to have a better response, PFS, and OS when treated with cetuximab or panitumumab.